Education in Process Systems Engineering: Why it matters more than ever and how it can be structured. (12th July 2019) - Cameron, Ian T.; Engell, Sebastian; Georgakis, Christos; Asprion, Norbert; Bonvin, Dominique; Gao, Furong; Gerogiorgis, Dimitrios I.; Grossmann, Ignacio E.; Macchietto, Sandro; Preisig, Heinz A.; Young, Brent R.
Highlights: Necessity of systems thinking – challenges, concepts and practice. Core elements of current PSE education. Curriculum Design: Goals and structures. Responses to present and future challenges. Abstract: This position paper is an outcome of discussions that took place at the third FIPSE Symposium in Rhodes, Greece, between June 20–22, 2016 (http://fi-in-pse.org ). The FIPSE objective is to discuss open research challenges in topics of Process Systems Engineering (PSE). Here, we discuss the societal and industrial context in which systems thinking and Process Systems Engineering provide indispensable skills and tools for generating innovative solutions to complex problems. We further highlight the present and future challenges that require systems approaches and tools to address not only 'grand' challenges but any complex socio-technical challenge. The current state of Process Systems Engineering (PSE) education in the area of chemical and biochemical engineering is considered. We discuss approaches and content at both the unit learning level and at the curriculum level that will enhance the graduates' capabilities to meet the future challenges they will be facing. PSE principles are important in their own right, but importantly they provide significant opportunities to aid the integration of learning in the basic and engineering sciences across the whole curriculum. This fact is crucial in curriculum design and implementation, such that our graduates benefit to the maximum extent from their learning.